Oxytocin and vasopressin in the human brain: social neuropeptides for translational medicine - Meyer-Lindenberg, Andreas; Domes, Gregor; Kirsch, Peter; Heinrichs, Markus (Nature reviews. Neuroscience, 2011)
The neuropeptides oxytocin (OXT) and arginine vasopressin (AVP) have had key roles throughout mammalian evolution in the regulation of complex social cognition and behaviours, such as attachment, social exploration, recognition and aggression, as well as anxiety, fear conditioning and fear extinction.The goal of this Review is to assess the OXT and AVP systems in the human brain from a translational viewpoint with regard to social behaviour, genetics, neuroimaging, neuroendocrinology and clinical studies.Neuropeptides can be non-invasively delivered to the human brain using intranasal administration, with clear behavioural- and neural systems-level consequences.Following intranasal administration, OXT improves emotion recognition, enhances gaze to the eye region, promotes trust and prosocial behaviour, and reduces behavioural and endocrine responses to social stress.In initial studies, intranasal administration of AVP seems to influence social communication and increase reactivity to social stress.Common genetic risk variants in the genes that encode the brain receptors for OXT and AVP have been associated with autism and social behavioural phenotypes in humans.Imaging genetics studies show that genetic risk variants in the brain receptors for OXT and AVP affect the structure and function of key regions for social behaviour, including the amygdala, anterior cingulate cortex and hypothalamus.Functional neuroimaging studies using intranasal application of neuropeptides support the view that the effects of OXT and AVP on social processing are mediated by limbic circuitry with the amygdala as a core structure.Recent studies have begun to provide evidence for impaired functioning of OXT and AVP in mental disorders that are characterized by early attachment disruption or social interaction pathology - for example, autism, social anxiety disorder, borderline personality disorder and schizophrenia - thereby providing new translational dimensions for novel pharmacological interventions in the neuropeptide system. We suggest that the key route to translational success is a synergistic combination of OXT administration (including selective and longer-acting OXT receptor agonists) with psychotherapy; a 'propsychotherapeutic' neuropharmacological approach that could be referred to as 'psychobiological therapy'.
Gesehen am 19.08.2022